Insomnia Promotes Hepatic Steatosis in Rats Possibly by Mediating Sympathetic Overactivation - Wang, Zongding; Liang, Xiaoyan; Lu, Yanmei; Jiang, Tiemin; Aji, Tuerganaili; Aimulajiang, Kalibixiati; Sun, Huaxin; Zhang, Ling; Zhou, Xianhui; Tang, Baopeng; Wen, Hao (Frontiers in Physiology, 2021)
Abstract Background: Insomnia is a widespread problem that can lead to the occurrence of other diseases and correlates closely with sympathetic nerve hyperactivation. Obesity-induced hepatic steatosis is mediated by sympathetic overactivation. However, it remains unclear whether insomnia may cause hepatic steatosis. The goal of this study was to preliminarily investigate whether insomnia caused hepatic steatosis in rats via sympathetic hyperactivation. Methods: A total of 32 Sprague-Dawley male rats were divided randomly into four groups: model, Sd, estazolam and control (8 rats/group). Model group received sustained sleep deprivation using the modified multiple platform method. In the Sd group, rats underwent sleep deprivation after receiving sympathetic denervation (Sd) by 6-hydroxydopamine (6-OHDA). Estazolam group: the rats concurrently received sleep deprivation and treatment with estazolam. The other eight rats housed in cages and kept in a comfortable environment were used as control. Blood samples were obtained for analysis of plasma lipids and hepatic function. Sympathetic hyperactivation-related indexes and hepatic steatosis in liver tissues were tested. Results: Liver enzymes, plasma lipid levels and hepatic steatosis were elevated in insomnia rats, and sympathetic hyperactivation was found. Insomnia-induced hepatic steatosis was effectively lowered with pharmacological ablation of the hepatic sympathetic nerves. Furthermore, the treatment of insomnia with estazolam inhibited sympathetic activation and reduced hepatic steatosis. Conclusion: Sustained sleep deprivation-induced insomnia promotes hepatic steatosis in rats possibly by mediating sympathetic overactivation